Tinjauan Pengembangan Formulasi Tablet Effervescent Ekstrak Tanaman dengan Variasi Konsentrasi Asam Dan Basa - Sulistyaningrum, Indriyati Hadi; Sayekti, Tyas Harnum; Rosyid, Abdur (Sultan Agung Islamic University of Semarang, 2024)
Background: The main ingredients of effervescent tablet formula are acids and bases which will produce CO2 and give a foamy bubble effect when mixed with water. The formulation requires an optimal acid-base composition to obtain tablets with good quality. This study aims to determine the formulation of effervescent tablets from the various plant’s extract with variations in acid and base based on a literature review. Methods: This research is a journal review conducted by analyzing journals to determine the formulation of the leaf form. using the PRISMA method. Journals obtained with the keywords “Formulation Effervescent Tablet” AND “Tablet Effervescent” AND “Formulation Effervescent Tablet with Variation Acid Base”. The journals selected are journals published in the last 10 years (2011-2021), full text and attaching formulas with variations in acid base along with the results of physical stability tests for granules and tablets. The databases used are Google Scholar, Scopus and Science Direct. There are 5 journals that meet the inclusion criteria. Results: The plant extract can be formulated into effervescent tablets using the wet granulation method, with a tablet weight of 1-2 grams. Conclusion: Citric acid and sodium bicarbonate can be chosen as reactants of acid and base with a ratio of 1: 3,11. The total acid and base used in the formulation was 55% of the total weight of the tablet.